Adiksi Internet Sebagai Salah Satu Dampak Negatif Pembelajaran Jarak Jauh Selama Masa Pandemi COVID-19 - Ratulangi, Annastasya G.; Kairupan, Bernabas H. R.; Dundu, Anita E. (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic causes a change in the learning process, in which schools must implement distance learning to prevent the spreading of the virus. In distance learning the use of internet will increase both for learning and for recreation. This situation could turn internet addiction as one of the negative impacts of distance learning during the COVID-19 pandemic. This study aims to determine internet addiction and internet use in students on distance learning during the COVID-19 pandemic.This research was made in the form of a literature review using three databases, namely Google Scholar, Pubmed, and ClinicalKey. The literatures should be in the form of English or Indonesian, created within this year (2020) and can be accessed in fulltext. Based on the result of 10 studies, it was found that there is an increase of internet use and internet addiction among student during the pandemic COVID-19. An increase of internet use has the potential to increase the internet addiction in the future. In conclusion, internet addiction is one of the negative impacts that can occur and increase on students during the COVID-19 pandemic.Keywords: internet addiction, student, distance learning, COVID-19 pandemicÂ Â Abstrak: Pandemi Coronavirus Disease 2019 (COVID-19) memberi perubahan dalam proses pembelajaran, di mana sekolah harus menerapkan pembelajaran jarak jauh untuk mencegah penyebaran virus. Dalam pembelajaran jarak jauh penggunaan internet akan meningkat, baik untuk pembelajaran maupun untuk rekreasi. Situasi ini dapat menjadikan adiksi internet menjadi salah satu dampak negatif pada pembelajaran jarak jauh selama pandemi COVID-19. Tujuan penelitian ini bertujuan untuk mengetahui adiksi internet dan penggunaan internet pada pelajar selama pembelajaran jarak jauh di masa pandemi COVID-19. Penelitian ini dibuat dalam bentuk literature review dengan menggunakan tiga database, yaitu Google Scholar, PubMed, dan ClinicalKey. Literatur yang akan digunakan dapat berbentuk Bahasa Inggris dan atau Bahasa Indonesia, dalam jangka waktu 1 tahun terakhir (2020) dan dapat diakses secara penuh. Berdasarkan hasil dari 10 penelitian, ditemukan adanya peningkatan penggunaan internet dan adiksi internet pada pelajar selama pandemi COVID-19. Peningkatan penggunaan internet ini dapat berpotensi meningkatkan adiksi internet di masa mendatang. Sebagai simpulan, adiksi internet merupakan salah satu dampak negatif yang dapat terjadi dan meningkat pada pelajar selama pembelajaran jarak jauh di masa pandemi COVID-19.Kata Kunci: adiksi internet, pelajar, pembelajaran jarak jauh, pandemi COVID-19